Bond behavior of recycled tire steel-fiber-reinforced concrete and basalt-fiber-reinforced polymer rebar after prolonged seawater exposure - Soltanzadeh, Fatemeh (2023)
The integration of basalt-fiber-reinforced polymer (BFRP) rebars into concrete design standards still remains unrealized due to limited knowledge on the performance of the rebars in concrete, particularly in terms of bond durability in harsh conditions. In this work, we investigated the bond durability characteristics of BFRP rebars in fiber-reinforced self-compacting concrete (FRSCC) structures. To this aim, a number of 24 FRSCC pullout specimens reinforced with either BFRP rebar or glass-fiber-reinforced polymer, GFRP, rebar, which is a commonly used type of FRP, were fabricated. Half of these specimens were submerged in simulated seawater for a two-year span, while the other 12 similar specimens were maintained in standard laboratory conditions for comparative purposes. Subsequently, all 24 specimens underwent monotonic and fatigue pull-out tests. The exploration in this study focused on investigating the influence of the environmental condition, reinforcement type, and loading type on the bond stress versus slip relationship, maximum bond stress, and failure mode of the specimens. Based on the results obtained and by adopting the durability approach of industry standards for prediction of the bond retention of FRP-reinforced concrete, the bond strength retention between BFRP/GFRP and FRSCC after 50 years of exposure to seawater was estimated. The outcomes of the study are expected to enhance engineersâ confidence in the use of FRP, especially BFRP, for constructing durable and sustainable reinforced concrete structures in aggressive environments.